Economic Evaluation Plan (EEP) for A Very Early Rehabilitation Trial (AVERT): An international trial to compare the costs and cost-effectiveness of commencing out of bed standing and walking training (very early mobilization) within 24 h of stroke onset with usual stroke unit care. Issue 4 (June 2016) - Sheppard, Lauren; Dewey, Helen; Bernhardt, Julie; Collier, Janice M; Ellery, Fiona; Churilov, Leonid; Tay-Teo, Kiu; Wu, Olivia; Moodie, Marj
Rationale: A key objective of A Very Early Rehabilitation Trial is to determine if the intervention, very early mobilisation following stroke, is cost-effective. Resource use data were collected to enable an economic evaluation to be undertaken and a plan for the main economic analyses was written prior to the completion of follow up data collection. Aim and hypothesis: To report methods used to collect resource use data, pre-specify the main economic evaluation analyses and report other intended exploratory analyses of resource use data. Sample size estimates: Recruitment to the trial has been completed. A total of 2, 104 participants from 56 stroke units across three geographic regions participated in the trial. Methods and design: Resource use data were collected prospectively alongside the trial using standardised tools. The primary economic evaluation method is a cost-effectiveness analysis to compare resource use over 12 months with health outcomes of the intervention measured against a usual care comparator. A cost-utility analysis is also intended. Study outcome: The primary outcome in the cost-effectiveness analysis will be favourable outcome (modified Rankin Scale score 0-2) at 12 months. Cost-utility analysis will use health-related quality of life, reported as quality-adjusted life years gained over a 12 month period, as measured by the modified Rankin Scale and the Assessment of Quality of Life. Discussion: Outcomes of the economic evaluation analysis will inform the cost-effectiveness of very early mobilisation following stroke when compared to usual care. The exploratory analysis will report patterns of resource use in the first year following stroke.